Adult and Adolescent Disclosures of Child Sexual Abuse: A Comparative Analysis - McGill, Lucy (Journal of interpersonal violence, 2023)
The recent attention focused on child sexual abuse (CSA) disclosure pathways has highlighted complex psychological processes that influence disclosure both for children and adults. Some authors have suggested that such processes may differ between children and adults yet few studies have examined distinct samples within the same study. This paper addresses this gap by exploring adolescent (n = 20) and adult (n = 10) experiences of disclosure of childhood sexual abuse. Interviews were conducted with both samples, using the same interview schedule and a comparative analysis was conducted of the key themes identified from a grounded theory analysis. Those themes that were found to be common to both samples included pressure cooker effect, telling would make it worse, and self-blame. Themes that were found to be more prevalent in the adolescent sample included police/court involvement, concern for other children, being asked, and peer influence. It is suggested that such potential differences reflect the changing social context over the past few decades which is characterised by increased awareness of sexual abuse as a crime and the risks of recidivism of offenders.